Study on homophobic bullying in Portugal using Multiple Correspondence Analysis (MCA) - Rodrigues, L. (2017)
Educational institutions, as well as political, social and scientific discourses, have contributed towards discrimination and violence against people with non-normative sexual orientations. Acts of violence among peers (bullying) motivated by homophobia occur on a frequent basis in school contexts. This study aims to identify the patterns in which homophobic bullying (victim identified) takes place in Portuguese schools using Multiple Correspondence Analysis. This study involved the application of a questionnaire to people of both sexes before obtaining a total of 171 participants reporting themselves as victims of homophobic bullying in schools. Following the identification of eight indicators and the selection of two dimensions, while also structuring the axes in accordance with the representation space, four patterns of homophobic bullying could be identified: masculine violence, feminine violence, violence with less perceived impact, and violence with greater perceived impact. These different patterns have allowed us to learn about the different ways in which peer violence takes place in schools and its possible effects. Among the main study conclusions, it is highlighted how male participants were victims of violence at an earlier age than female participant victims. Another key finding is the complete lack of cases in which the aggressors were only female. Finally, a common conclusion to all participants, encapsulates how none of the victims reported the violence to their families for fear of losing family support by revealing a non-heterosexual orientation.